Comparative study of mesoporous NixMn6−xCe4 composite oxides for NO catalytic oxidation. Issue 53 (1st October 2019) - Weiman, Li; Haidi, Liu; Min, Zhang; Yunfa, Chen
Abstract : In this work, a series of mesoporous Ni x Mn6− x Ce ternary oxides were prepared to investigate their NO catalytic oxidation ability. Abstract : In this work, a series of mesoporous Ni x Mn6− x Ce ternary oxides were prepared to investigate their NO catalytic oxidation ability. The sample Ni2 Mn4 Ce4 showed a 95% NO conversion at 210 °C (GHSV, ∼80 000 h −1 ). Characterization results showed the good catalytic performance of Ni2 Mn4 Ce4 was due to its high specific surface area, more surface oxygen and high valance manganese species, which can be ascribed to the incorporation of three elements. Based on the results of XRD, H2 -TPR, O2 -TPD and XPS, we confirmed the existence of Ni 3+ + Mn 3+ → Ni 2+ + Mn 4+, Ce 4+ + Ni 2+ → Ce 3+ + Ni 3+ in Ni2 Mn4 Ce4, and the oxidation–reduction cycles were proved to be helpful for NO oxidation. The results from an in situ DRIFTS study indicated the presence of bidentate nitrate and monodentate nitrate species on the catalyst's surface. The nitrate species were proved to be intermediates for NO oxidation to NO2 . A nitrogen circle mechanism was proposed to explain the possible route for NO oxidation. Nickel introduction was also helpful to improve the SO2 resistance of the NO oxidation reaction. The activity drop of Ni2 Mn4 Ce4 was 13.15% in the presence of SO2, better than Mn6 Ce4 (25.29%).